2011
DOI: 10.1002/dc.21348
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of SOX9 is related with the progression of gastric carcinoma

Abstract: To investigate the SOX9 expression and its effects on promoting invasion and metastasis in the primary gastric adenocarcinomas. One hundred and eighty six patients with primary gastric adenocarcinomas who underwent surgery between 2002 and 2006 were classified as low, intermediate, and high SOX9 expression groups by immunohistochemistry (IHC). Our IHC performance showed that SOX9 was lowly expressed in lower crypt of the normal epithelium adjacent to the tumor, and SOX9 expression was also observed in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…In the present study, it was revealed that SOX9 knockdown led to suppressed cell proliferation and increased cell apoptosis, indicating that SOX9 is a tumor promoter in AEG. This finding is consistent with the role of SOX9 in other types of tumor (20)(21)(22). It has previously been reported that SOX9 mediates the effect of certain antitumor drugs; SOX9 expression was markedly inhibited in mice tumors by combination treatment with ABT-263 and 5-FU (24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, it was revealed that SOX9 knockdown led to suppressed cell proliferation and increased cell apoptosis, indicating that SOX9 is a tumor promoter in AEG. This finding is consistent with the role of SOX9 in other types of tumor (20)(21)(22). It has previously been reported that SOX9 mediates the effect of certain antitumor drugs; SOX9 expression was markedly inhibited in mice tumors by combination treatment with ABT-263 and 5-FU (24).…”
Section: Discussionsupporting
confidence: 91%
“…The importance of SOX9 in tumorigenesis has been identified, and the dysregulation of SOX9 has been implicated in several cancers, including prostate cancer, lung adenocarcinoma and gastric carcinoma (20)(21)(22). Overexpression of SOX9 has been demonstrated to increase tumor growth, invasion and angiogenesis (14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, increased mortality associated with elevated SOX9 has been observed in numerous cancers, including separate cohorts of colon and rectal cancer (Lü et al , 2008; Zhou et al , 2011; Matheu et al , 2012; Mazur et al , 2012). Many studies report mechanistic roles for SOX9 in cancer promotion, specifically in apoptotic resistance, neoplastic transformation and proliferation in glioma, colorectal and prostate cancer (Bastide et al , 2007; Matheu et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, SOX9 regulates proliferation, differentiation and metastasis (Bastide et al , 2007; Matheu et al , 2012). Clinical studies in breast, gastric biliary tract and CRC indicate poorer prognosis with tumour SOX9 overexpression (Lü et al , 2008; Zhou et al , 2011; Matheu et al , 2012; Mazur et al , 2012). Hence, considering the mechanistic evidence for the roles of HEY1, HES1 and SOX9 in cancer pathogenesis and the preclinical data implicating Notch signalling chemotherapy responsiveness, we set out to characterise the expression of these NTFs in CRC and to explore a potential role in chemotherapy resistance.…”
mentioning
confidence: 99%
“…SOX9 expression is upregulated by PGD2, and ectopic SOX9 expression has been shown to suppress growth of ovarian cancer and melanoma cells in vitro and/or in vivo [32]. However, both aberrant SOX9 expression in carcinoma tissues and elevated SOX9 expression are correlated to disease progression and poor prognosis for hepatocellular carcinoma, gastric cancer and prostate cancer [33-35]. SOX9 protein levels are elevated in invasive human uroepithelial carcinoma tissues, which are induced by the activation of epidermal growth factor receptor [34].…”
Section: Introductionmentioning
confidence: 99%